Histological Changes in the Kidney of Sciades Herzbergii (Siluriformes, Ariidae) for Environmental Monitoring of a Neotropical Estuarine Area (São Marcos Bay, Northeastern Brazil) - da Silva Castro, Jonatas; França, Caroline Lopes; de Lima Cardoso, Rayssa [UNESP]; da Silva, Wendell Melquias Medeiros Leal; de Santana, Thiago Campos; Santos, Débora Martins Silva; Carvalho-Neta, Raimunda Nonata Fortes; Teixeira, Erivânia Gomes (Springer Nature, 2019)
The aim of this study was to evaluate the environmental quality of a port in Brazil using the renal alterations in Sciades herzbergii as biomarkers of aquatic contamination. Samples of S. herzbergii were collected in two areas in São Marcos Bay, Brazil: (A1) Itaqui Port (potentially impacted area); and (A2) Puca Creek (control area). At the same time, the abiotic data was obtained, in addition to the sampling of water for metals analysis. The fish kidney of each specimen was submitted to the usual histological technique. It was possible to identify alterations such as melanomacrotic centers, dilation of the glomeruli, capillary endothelium gap, occlusion of the tubular lumen, immature nephron and dilated vessels. Samples of S. herzbergii collected in the port region showed a higher frequency of renal alterations, indicating that the organisms present in that region are probably suffering due to the impacts caused by the port activities.
Keywords: Biomarkers; Catfish; Environmental impact; Port complex